Sistem Informasi Antrian Periksa Dokter Di Rumah Sakit Umum Pidie Jaya Menggunakan Metode FIFO Berbasis Android - Azhar (Jurnal Elektro dan Informatika, 2021)
The Pidie Jaya Regional Public Hospital is a health service institution that organizes individual health services in a comprehensive manner that provides inpatient, outpatient and emergency services. The queue for outpatient often accumulate when queuing to get the queue number for Doctor's services and get medicines at the Pharmacy. Design and created The Information System of the queue for Doctor's examination in Pidie Jaya Regional Public Hospital Using the Android-Based FIFO Method has has aim to find out how long are the queue can be minimized and help patients to obtain the online queue number. To design, created and implement The Information System of the queue for Doctor's examination in Pidie Jaya Regional Public Hospital Using the Android-Based FIFO Method. This research uses two queuing models, there are a single channel multiple phase and multiple phase single channel. FIFO (First-In First-Out) Method was applied based on the patient who registers for the first time will get the first service and finished the first service or patient who registers for the first time will get a queue number. Based on the results of testing the queue information system, it can make it easier for outpatients to get the doctor's check queue number and queue at the pharmacy online, and can improve the patient service system at Pidie Jaya General Hospital. The result of this research is an android application that is used by hospital officers and patients seeking treatment at the Pidie Jaya public hospital in obtaining queue information and prescriptions, this application is also equipped with a realtime database to facilitate the process of exchanging information between users directly at system.